Intercellular Adhesion Molecule 1 Regulates Left Ventricular Leukocyte Infiltration, Cardiac Remodeling, and Function in Pressure Overload–Induced Heart Failure. Issue 3 (March 2016) - Salvador, Ane M.; Nevers, Tania; Velázquez, Francisco; Aronovitz, Mark; Wang, Bonnie; Abadía Molina, Ana; Jaffe, Iris Z.; Karas, Richard H.; Blanton, Robert M.; Alcaide, Pilar
Abstract : Background: Left ventricular dysfunction and heart failure are strongly associated in humans with increased circulating levels of proinflammatory cytokines, T cells, and soluble intercellular cell adhesion molecule 1 (ICAM1). In mice, infiltration of T cells into the left ventricle contributes to pathological cardiac remodeling, but the mechanisms regulating their recruitment to the heart are unclear. We hypothesized that ICAM1 regulates cardiac inflammation and pathological cardiac remodeling by mediating left ventricular T‐cell recruitment and thus contributing to cardiac dysfunction and heart failure. Methods and Results: In a mouse model of pressure overload–induced heart failure, intramyocardial endothelial ICAM1 increased within 48 hours in response to thoracic aortic constriction and remained upregulated as heart failure progressed. ICAM1‐deficient mice had decreased T‐cell and proinflammatory monocyte infiltration in the left ventricle in response to thoracic aortic constriction, despite having numbers of circulating T cells and activated T cells in the heart‐draining lymph nodes that were similar to those of wild‐type mice. ICAM1‐deficient mice did not develop cardiac fibrosis or systolic and diastolic dysfunction in response to thoracic aortic constriction. Exploration of the mechanisms regulating ICAM1 expression revealed that endothelial ICAM1 upregulation and T‐cell infiltration were not mediated by endothelial mineralocorticoid receptor signaling, as demonstrated in thoracic aortic constriction studies in mice with endothelial mineralocorticoid receptor deficiency, but rather were induced by the cardiac cytokines interleukin 1β and 6. Conclusions: ICAM1 regulates pathological cardiac remodeling by mediating proinflammatory leukocyte infiltration in the left ventricle and cardiac fibrosis and dysfunction and thus represents a novel target for treatment of heart failure.